Оцінка впливу виробничих факторів на якість продукції цифрової друкарні «МАДРИД» - Донський, Д. О.; Манаков, В. П.; Чеботарьова, І. Б. (ТОВ «Видавництво Ліра-К», 2025)
The paper analyzes the production factors of the digital printing house «Madrid» and their impact on various stages of the printing process. The reasons that affect the quality of products are ranked by the expert method of pairwise comparisons and the most important ones are identified.
Keywords: цифрова друкарня; якість продукції